THE ADAPTATION OF RICK RIORDAN’S PERCY JACKSON AND THE OLYMPIANS: THE SEA OF MONSTERS NOVEL INTO FILM - Muhammad Ghifari Rizki Pratama; Hasbi Assiddiqi (Saksama, 2022)
Adaptation is the process of adapting a novel into a film. The emergence of the phenomenon of adaptation of novels into film form is a substantial change in discourse that gave rise to the term Adaptation. Percy Jackson and the Olympians: The Sea of Monsters novel is a popular novel that is good to be adapted into a film. The novel and film are the second installment in the Percy Jackson and the Olympians series after Percy Jackson and the Olympians: The Lightning Thief. Currently, the adaptation process is becoming increasingly important to analyze because the adaptation process can provide interpretation and comparison between novels and films. The adaptation in literary field is become normal as there are a lot of works that produced with helps of adaptation. One of many adaptations case that happens is the shifting process from written literary works into the films, which will produce some changes and variations on its adaptation and that is the interesting topic to be discussed.This study examines the intrinsic adaptation of the elements in it. This study uses a descriptive qualitative method because the research data is in the form of images and text. The data from this study are several pictures from a film as well as excerpts from novels. This study uses the adaptation theory from Eneste Pamusuk and the Structuralism theory from Ferdinand de Saussure. The results of the research show that there have been subtractions, additions, and varied changes to the plot and setting in the film. The plot sequence in Percy Jackson: The Sea of Monsters underwent many changes. In the process of intrinsic element adaptation, the writer found 1 character who experienced a reduction in the film out of a total of 12 characters, Equalization of points of view from novel to film, 1 addition of the theme of friendship, 5 plots that were reduced, 8 plots that were added 1 subplot that was reduced, and 3 flow changes vary. In addition, the setting in the film Percy Jackson: Sea of Monsters also underwent many changes. In the process of adaptation the settings, the writer found 11 backgrounds that were reduced, 7 settings that were added, and 1 setting that underwent various changes. In this study, the authors found several influences related to the process of adaptation of intrinsic elements.First, when adaptations occur on intrinsic elements, not too many changes occur in the film. This change makes the film acceptable and in demand by the audience. Second, when several parts that are quite influential in the plot and setting are removed or changed, important things related to the story are eventually lost. Third, adaptations made in film settings provide many real-life images that novels cannot explain. The setting in the novel is made to look real and very good. Fourth, this film was closer to the tastes and conditions of society at that time, so that this film was more acceptable to the public.